Reply to Truffot et al - Mahmoudi, Mazyar; Brenner, Thorsten; Hatiboglu, Gencay; Burhenne, Jürgen; Weiß, Johanna; Weigand, Markus A.; Haefeli, Walter E. (Clinical infectious diseases, 2018)
To the editor - In their letter to Clinical Infectious Diseases, Truffot and coworkers suggest that the recently reported changes in voriconazole dose requirement
Published: 27 January 2018
Reaktion auf: Truffot, A., Thiebaut-Bertrand, A., Chapuis, C., Stanke-Labesque, F., Gautier-Veyret, E.: Inhibition of voriconazole metabolism by meropenem: a role for inflammation?
Gesehen am 16.09.2019